PENGARUH TERAPI BEKAM TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI: PENGARUH TERAPI BEKAM TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI - Istighfaroni, Mohammad Farid; Wijaya, Arif; Roni, Faishol (LPPM STIKes Bahrul Ulum Jombang, 2021)
The method of healing hypertension cupping is based on the activation of body organs. Where organisms are implanted, such as the liver, kidney, and heart, can be arranged by choosing the right location to stabilize blood pressure so that it can help treat people with high blood pressure. Literature review is an effective evaluation strategy for cupping treatment with blood pressure in hypertensive patients. Literature review. Using a systematic review, I searched an electronic database (Google Scholar) for previous research published between 2010-2020. Some of the keywords used include cupping therapy, blood pressure and hypertension. Manual review of abstracts was used to summarize the article selection process. A total of 365 articles were identified. Researchers found 10 articles with inclusion and exclusion criteria that were met in the review. Respondents have hypertension and have received cupping therapy. Cupping treatment has an impact on hypertensive patients by lowering their blood pressure. This research can develop further to be researched by qualitative and quantitative methods.